2020
DOI: 10.24036/jelt.v9i1.107957
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Difficulties in Listening Comprehension: A Descriptive Study at English Language and Literature Department FBS UNP

Abstract: This research was aimed to find out the difficulties that mostly faced by students in listening comprehension and the factors which cause the difficulties at English language and literature department FBS UNP. This study employed descriptive qualitative research method. The subjects of this research were K-2 Class which consists of 32 students selected by using cluster sampling technique. The data was collected from questionnaire and interview. The researcher distributed the questionnaire to all members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 2 publications
3
9
0
Order By: Relevance
“…Meanwhile, the listening material as the second problems often occoured in this research and its in line with Erzad (2020) research, there were some problems related to listening in Students IAIN Kudus such as speedy of speech and lengt of listening in coherence with listening material. In addition, the speaker and the setting was the most variables problems occoured in the research and its mutually supported with Diora (2020) in his previous research related to students FBS UNP listening problems were reveled speaker and physical setting as the most variable encountered by students.…”
Section: Students Difficulties Related To the Speaker And Physical Se...supporting
confidence: 67%
See 2 more Smart Citations
“…Meanwhile, the listening material as the second problems often occoured in this research and its in line with Erzad (2020) research, there were some problems related to listening in Students IAIN Kudus such as speedy of speech and lengt of listening in coherence with listening material. In addition, the speaker and the setting was the most variables problems occoured in the research and its mutually supported with Diora (2020) in his previous research related to students FBS UNP listening problems were reveled speaker and physical setting as the most variable encountered by students.…”
Section: Students Difficulties Related To the Speaker And Physical Se...supporting
confidence: 67%
“…In finding the answer of the difficulties, factors caused to students in listening skill, so the researcher determined to employe qualitative descriptive for this research, according to Selinger and Shohamy (Diora & Rosa, 2020) descriptive qualitative is the investigating research and it can be employed by some instrument . As well known that qualitative reseach instrument employ some instrument such as questionnaire, interview and observation for qualitative method most of them, but, actually in this case the researcher only use questionnaire for gaining and collecting the data .the questionnaire used to collect some data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the students' ability to listen to complex sentences is extremely disreputable because they lack grammar. (Diora & Rosa, 2020) found that some of the students did not master grammar structure because they thought it was totally hard to do. As well in listening, students found it difficult because the listening text has complexed grammatical structures and the students were hard to understand about it.…”
Section: Discussionmentioning
confidence: 99%
“…People normally listen for many purposes, for example, for entertainment, academic purposes, and getting important information. Furthermore, Diora & Rosa (2020) assert that learning listening will let people extremely advance their communication skills through the process of obtaining information from the speaker says, forming and representing the meaning, discussing the meaning with the speaker and answering it, and producing the meaning through participation, creativity, and empathy (Gilakjani & Sabouri, 2016). Accordingly, Sulistyani (2014) emphasizes that if the capacity to understand the spoken form of a foreign language is not learned naturally, this receptive skill must be taught.…”
Section: Introductionmentioning
confidence: 99%